Optimization of spiral continuous flow-through pulse light sterilization for Escherichia coli in red grape juice by response surface methodology. (November 2019) - Xu, Feifei; Wang, Bei; Hong, Chen; Telebielaigen, Shabuerbieke; Nsor-Atindana, John; Duan, Yuqing; Zhong, Fang
Abstract: The effect of a spiral continuous flow-through pulsed light (PL) system on the inactivation of Escherichia coli in red grape juice was evaluated. The grape juice was treated with different numbers of pulses, intensities of PL and liquid flow rates. Reduction of E. coli was determined by plate counting method. Response surface methodology was used to analyze the correlation among the factors. The results showed the inactivation effect increased with intensities and pulse numbers. Middle speed of flow rate could obtain the highest inactivation effect. Reductions of 2.1, 2.6 and 3.7 log were achieved in treatment of 100 pulses, 30 mL/min flow rate, intensities of 0.13, 0.40 and 0.66 J/cm 2 /pulse, respectively. Reductions of 1.0, 3.1 and 1.7 log were achieved in treatment of 100 pulses, 0.66 J/cm 2 /pulse, flow rates of 0, 30 and 60 mL/min, respectively. As verifying tests from the optimization exercise, with the spiral continuous flow-through PL treatment, the number of E. coli reduced by 4.89 log CFU/mL at the optimal levels of 80 pulses, intensity of 0.66 J/cm 2 /pulse and flow rate of 40 mL/min. These results suggest that the spiral continuous flow PL could improve the inactivation of E. coli in red grape juice. Highlights: Spiral continuous flow-through pulsed light greatly inactive E. coli in grape juice. Pulse number, intensity and flow rate affect the inactivation effect. Numbers of E. coli reduced by 4.89 log CFU/mL at the optimal level by RSM.